XPS Characterization of Fiber Surface of Chemithermomechanical Pulp Fibers Modified by White-Rot Fungi - Huang, Chongxing; Yang, Qifeng; Wang, Shuangfei (Asian Journal of Chemistry, 2012)
In the present paper, the fiber surface chemistry of eucalyptus chemithermomechanical pulp fibers before and after fungal modification was studied with X-ray photoelectron spectroscopy. The results show that the fungal modified chemithermomechanical pulp fibers had a higher O/C ratios and lower C1 percentage than the control pulp fibers and the C1s peak shifted to high binding energy direction. This implies that fungal modified fibers have less lignin and extractives and more hydrophilic groups and carbohydrate on the surface, which is preferred in helpful to forming hydrogen bond. The X-ray photoelectron spectroscopy quantified analysis of surface lignin and extractives contents showed that the content of lignin and extractives contents of fungal modified fiber decreased by 8.3 % and 55.9 %, respectively. However, bulk lignin and extractives contents of fungal modified fiber decreased only by 2.5 % and 11.1 %, respectively. This indicated that the degradation of lignin and extractives mainly took place on fiber surface.